Scd1 and monounsaturated lipids are required for autophagy and survival of adipocytes - Hiroyuki Mori; Sydney K. Peterson; Rachel C. Simmermon; Katherine A. Overmyer; Akira Nishii; Emma Paulsson; Ziru Li; Annie Jen; Romina M. Uranga; Jessica N. Maung; Warren T. Yacawych; Kenneth T. Lewis; et al. (Elsevier, 2024)
Objective: Exposure of adipocytes to 'cool' temperatures often found in the periphery of the body induces expression of Stearoyl-CoA Desaturase-1 (Scd1), an enzyme that converts saturated fatty acids to monounsaturated fatty acids. The goal of this study is to further investigate the roles of Scd in adipocytes. Method: In this study, we employed Scd1 knockout cells and mouse models, along with pharmacological Scd1 inhibition to dissect the enzyme's function in adipocyte physiology. Results: Our study reveals that production of monounsaturated lipids by Scd1 is necessary for fusion of autophagosomes to lysosomes and that with a Scd1-deficiency, autophagosomes accumulate. In addition, Scd1-deficiency impairs lysosomal and autolysosomal acidification resulting in vacuole accumulation and eventual cell death. Blocking autophagosome formation or supplementation with monounsaturated fatty acids maintains vitality of Scd1-deficient adipocytes. Conclusion: This study demonstrates the indispensable role of Scd1 in adipocyte survival, with its inhibition in vivo triggering autophagy-dependent cell death and its depletion in vivo leading to the loss of bone marrow adipocytes.